2015
DOI: 10.1515/ngoe-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Training Programs for Managing Well-being in Companies

Abstract: This paper discussed the significance of well-being (WB) and well-being management (WBM). As successful WBM requires the implementation of different training programs, such programs are presented in detail. The cause-effect relationship between training and individual/organizational performance is researched as well. The aim of the research to support this article was to present WBM, its training programs, as well as the determination of WBM activities concerning the mentioned programs implemented in Slovenian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Results revealed that the group training model increased good health and sexual well-being, which was consistent with the hypothesis. Moreover, the research of Treven et al (Treven et al, 2015) on the training program to develop well-being in the organization, which was conducted with 320 employees who participated in stress management programs, diversity management programs, wellness programs, employee assistance programs, and programs for personal growth reported that the program could maximize happiness and wellness to employees. In addition, it was consistent with the research of Tabitha et al (Tabitha et al, 2015) that investigated the development of physical, mental, and spiritual health with the wellness development program for college counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Results revealed that the group training model increased good health and sexual well-being, which was consistent with the hypothesis. Moreover, the research of Treven et al (Treven et al, 2015) on the training program to develop well-being in the organization, which was conducted with 320 employees who participated in stress management programs, diversity management programs, wellness programs, employee assistance programs, and programs for personal growth reported that the program could maximize happiness and wellness to employees. In addition, it was consistent with the research of Tabitha et al (Tabitha et al, 2015) that investigated the development of physical, mental, and spiritual health with the wellness development program for college counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Even while work is becoming a major topic of conversation, research suggests that striking a balance is even more crucial for organizations and the workforce (Chaudhuri et al, 2020). Because of the turbulence in the business environment, it is common for employees to be on the verge of burnout and anxiety (Treven et al, 2015). Therefore, the recognition that well-being metrics offer essential insights into people's quality of life is what is driving the increased interest in the field (Oginni et al, 2023).…”
Section: Work and Well-beingmentioning
confidence: 99%
“…Talent development has been shown to help both the employee and the organization by favorably influencing employee performance by developing employee knowledge, skills, ability, competence and conduct (Manning, 2015;Treven et al, 2015). Haryonoa et al (2020) noted that employee competencies change through effective training programs.…”
Section: Relationship Between Talent Management and Task Performancementioning
confidence: 99%